2014
DOI: 10.4111/kju.2014.55.2.112
|View full text |Cite|
|
Sign up to set email alerts
|

The Efficacy and Safety of Tadalafil 5 mg Once Daily in the Treatment of Erectile Dysfunction After Robot-Assisted Laparoscopic Radical Prostatectomy: 1-Year Follow-up

Abstract: PurposeTo evaluate the efficacy and safety of tadalafil 5 mg once daily use in the treatment of erectile dysfunction (ED) after robot-assisted laparoscopic radical prostatectomy (RALP).Materials and MethodsThe study retrospectively evaluated 92 patients who underwent RALP at Dong-A University Hospital. The patients were surveyed by use of the abridged five-item version of the International Index of Erectile Function (IIEF-5) questionnaire, which was self-administered before surgery and at 6 months and 1 year a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Five articles lacked useful data. In all, six articles involving a total of 1678 patients (Montorsi et al ., , , ; Padma‐Nathan et al ., ; Mulhall et al ., ; Seo et al ., ), reporting data from a total of six RCTs, were included in the analysis: two RCTs compared PDE5 inhibitors (tadalafil 20 mg on demand and avanafil 100 mg on demand) with a placebo over the short term (≤6 months), and four RCTs compared PDE5 inhibitors (sildenafil 50 mg once daily, avanafil 10 mg nightly or 10 mg on demand and tadalafil 20 mg on demand or 5 mg once daily) with a placebo over the long term (9–12 months) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Five articles lacked useful data. In all, six articles involving a total of 1678 patients (Montorsi et al ., , , ; Padma‐Nathan et al ., ; Mulhall et al ., ; Seo et al ., ), reporting data from a total of six RCTs, were included in the analysis: two RCTs compared PDE5 inhibitors (tadalafil 20 mg on demand and avanafil 100 mg on demand) with a placebo over the short term (≤6 months), and four RCTs compared PDE5 inhibitors (sildenafil 50 mg once daily, avanafil 10 mg nightly or 10 mg on demand and tadalafil 20 mg on demand or 5 mg once daily) with a placebo over the long term (9–12 months) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Recently, much attention has focused on penile rehabilitation through the use of oral phosphodiesterase type 5 inhibitors or intracavernous injection of vasoactive agents in patients with ED after radical prostatectomy, because the prolonged hypoxia resulting from the neurogenic elimination of nocturnal erections might lead to cavernous endothelial and smooth muscle apoptosis and fibrosis. 6,7 Daily sildenafil administration was reported to improve nocturnal penile tumescence and rigidity, and erectile function in men who underwent nerve-sparing radical prostatectomy for prostate cancer. 8 However, the exact molecular mechanisms by which the restoration of nocturnal penile erection affects erectile function remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…For the long-acting PDE5-inhibitor tadalafil, an initial retrospective study in 92 patients showed that tadalafil OaD started early after robot-assisted laparoscopic nsRP was well tolerated and significantly improved EF compared to patients without PDE5-inhibitor treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%